Impacts of Corruption to Governmental Efficiency in 2015: Case to Latin America Countries - Barros, Emanoel de Souza (2019)
This paper seeks analyzing the impact of control of corruption on governmental efficiency of 33 countries in Latin America and Caribbean. The data were collected from World Bank (web platform) to 2015. Besides to a descriptive analysis, this paper added two regressions, one OLS and one Tobit, to confirm the effects of corruption control on government efficiency of the countries analyzed. Results show that the corruption framework is endemic in Latin America and Caribbean. Regressions models was estimated considering governmental efficiency score as a function of six explanatory variables (control of corruption, public spending with health, economic contractions, CPI-2010-2015, governmental consumption and public administration in government spending). Results confirm that there are positive relationship between control of corruption and governmental efficiency and identifying the control of corruption like cause of governmental (in)efficiency.